Activation, Urban Form, and Participation: The Case of the Informal Settlement Sinaí, Montes de Oca (Costa Rica) - Villalta Flórez-Estrada, Mario (2024)
The article provides an analysis of urban activation processes through morphological transformations in the informal neighborhood Sinai, located in San Jose, Costa Rica. These activations have been part of a multi-year participatory process facilitated by the Community Work Program TCU-708 of the School of Architecture at the University of Costa Rica. Within the analysis presented, topics such as the significance of daily use of public space, negotiation processes involving various stakeholders, and the interaction between urban morphology and participatory management processes are addressed. The crucial role of community infrastructure projects is explored, demonstrating how they can serve as catalysts for addressing various social and economic challenges faced by communities exposed to the most vulnerable conditions.